Graph Drawing 20th International Symposium, GD 2012, Redmond, WA, USA, September 19-21, 2012, Revised Selected Papers - Didimo, Walter.; Didimo, Walter.; Patrignani, Maurizio.; Patrignani, Maurizio. (Theoretical Computer Science and General Issues ;, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 20th International Symposium on Graph Drawing, GD 2012, held in Redmond, WA, USA, in September 2012. The 42 revised full papers presented together with 4 revised short papers and 8 poster descriptions were carefully reviewed and selected from 92 submissions. They cover a wide range of topics in two main tracks: combinatorial and algorithmic aspects, and visualization systems and interfaces. In addition, reports of the 19th Annual Graph Drawing Contest, which was held during the conference, and of a workshop on theory and practice of graph drawing to celebrate Professor Peter Eades' 60th birthday are included in the volume.